ANALISIS ALIRAN TRANSONIK BERDASARKAN PERSAMAAN ATUR TRANSONIK GANGGUAN KECIL - Kresna Sekar , Widjaja
Design of a transonic aircraft required an aerodinamics design and calculation methods to predict the aerodynamic forces in the transonic regime which is inherently nonlinear due to the pressence of the shock waves in the flow fields. This thesis describes unsteady transonic flow analysis based upon Transonic Small Disturbance (TSD) equation, which is the lowest equation in the governing equation hierarchs that can still represent the nonlinear structure of the flows. Method of solution adopted in this thesis is a Finite Difference Method based upon Approximate Factorization (Al) Algorithm. This method consist of two iteration step in time domain which are Time Accurate Step and Time Linearized Step. Validation of results with respect to both experimental and Euler and Full Potential numerical results are carried out for both two and three dimensional flows for steady cases. Mean while, validation for unsteady cases in time and frequency domain are carried out by Pulse Transfer Function Methods utilizing time to frequency domain of Fourier transformation. Analysis of aeroelastics phenomena such as flutter in the transonic regime is also described.